Impairments in age-dependent ubiquitin proteostasis and structural integrity of selective neurons by uncoupling Ran GTPase from the Ran-binding domain 3 of Ranbp2 and identification of novel mitochondrial isoforms of ubiquitin-conjugating enzyme E2I (ubc9) and Ranbp2. (4th March 2019) - Patil, Hemangi; Yoon, Dosuk; Bhowmick, Reshma; Cai, Yunfei; Cho, Kyoung-in; Ferreira, Paulo A.
ABSTRACT: The Ran-binding protein 2 (Ranbp2/Nup358) is a cytoplasmic and peripheral nucleoporin comprised of 4 Ran-GTP-binding domains (RBDs) that are interspersed among diverse structural domains with multifunctional activities. Our prior studies found that the RBD2 and RBD3 of Ranbp2 control mitochondrial motility independently of Ran-GTP-binding in cultured cells, whereas loss of Ran-GTP-binding to RBD2 and RBD3 are essential to support cone photoreceptor development and the survival of mature retinal pigment epithelium (RPE) in mice. Here, we uncover that loss of Ran-GTP-binding to RBD3 alone promotes the robust age-dependent increase of ubiquitylated substrates and S1 subunit (Pmsd1) of the 19S cap of the proteasome in the retina and RPE and that such loss in RBD3 also compromises the structural integrity of the outer segment compartment of cone photoreceptors only and without affecting the viability of these neurons. We also found that the E2-ligase and partner of Ranbp2, ubc9, is localized prominently in the mitochondrial-rich ellipsoid compartment of photoreceptors, where Ranbp2 is also known to localize with and modulate the activity of mitochondrial proteins. However, the natures of Ranbp2 and ubc9 isoforms to the mitochondria are heretofore elusive. Subcellular fractionation, co-immunolocalization and immunoaffinity purification of Ranbp2 complexes show that novel isoforms of Ranbp2 and ubc9 with molecular masses distinct from the large Ranbp2 and unmodified ubc9 isoforms localize specifically to the mitochondrial fraction or associate with mitochondrial components, whereas unmodified and SUMOylated Ran GTPase are excluded from the mitochondrial fraction. Further, liposome-mediated intracellular delivery of an antibody against a domain shared by the mitochondrial and nuclear pore isoforms of Ranbp2 causes the profound fragmentation of mitochondria and their delocalization from Ranbp2 and without affecting Ranbp2 localization at the nuclear pores. Collectively, the data support that Ran GTPase-dependent and independent and moonlighting roles of Ranbp2 or domains thereof and ubc9 control selectively age-dependent, neural-type and mitochondrial functions.